The Relationship Between Menstrual Cycle Disorders In Obese Adolescents - Oklin Dawa; Marliah Abdullah (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
Menstrual cycle disorders are the main symptom of anovulation, a phenomenon accompanied by decreased ovarian steroid secretion and production. Weight gain and an increase in adipose tissue in obese women, especially in the midsection, can disrupt the balance of steroid hormones such as androgens, estrogens, and sex hormone-binding globulins, which can affect the menstrual cycle in adolescents. The mechanism of obesity that is most often associated with menstrual cycle disorders. On that basis, this study aims to assess the relationship between insulin resistance and menstrual cycle disorders in obese adolescents. Method : This study used a cross-sectional design with comparisons where in this study the researchers compared the levels of the Homeostatic Model obese adolescent women who had normal menstrual cycles and abnormal menstrual cycles. Result : the group with abnormal menstrual cycles were found to be lower than those in the normal menstrual cycle group, but no significant difference was found. In addition, the abnormal menstrual cycle group were found to be lower but not significant. Conclusion : Obesity no significant relationship to the menstrual cycle in obese adolescent girls